Cyclin-dependent kinase 5 modulates the P2X2a receptor channel gating through phosphorylation of C-terminal threonine 372. Issue 11 (November 2017) - Coddou, Claudio; Sandoval, Rodrigo; Castro, Patricio; Lazcano, Pablo; Hevia, Maria José; Rokic, Milos; Hall, Bradford; Terse, Anita; Gonzalez-Billault, Christian; Kulkarni, Ashok B.; Stojilkovic, Stanko S.; Utreras, Elias
Abstract : Abstract: The purinergic P2X2 receptor (P2X2R) is an adenosine triphosphate–gated ion channel widely expressed in the nervous system. Here, we identified a putative cyclin-dependent kinase 5 (Cdk5) phosphorylation site in the full-size variant P2X2aR ( 372 TPKH 375 ), which is absent in the splice variant P2X2bR. We therefore investigated the effects of Cdk5 and its neuronal activator, p35, on P2X2aR function. We found an interaction between P2X2aR and Cdk5/p35 by co-immunofluorescence and co-immunoprecipitation in HEK293 cells. We also found that threonine phosphorylation was significantly increased in HEK293 cells co-expressing P2X2aR and p35 as compared to cells expressing only P2X2aR. Moreover, P2X2aR-derived peptides encompassing the Cdk5 consensus motif were phosphorylated by Cdk5/p35. Whole-cell patch-clamp recordings indicated a delay in development of use-dependent desensitization (UDD) of P2X2aR but not of P2X2bR in HEK293 cells co-expressing P2X2aR and p35. In Xenopus oocytes, P2X2aRs showed a slower UDD than in HEK293 cells and Cdk5 activation prevented this effect. A similar effect was found in P2X2a/3R heteromeric currents in HEK293 cells. The P2X2aR-T372A mutant was resistant to UDD. In endogenous cells, we observed similar distribution between P2X2R and Cdk5/p35 by co-localization using immunofluorescence in primary culture of nociceptive neurons. Moreover, co-immunoprecipitation experiments showed an interaction between Cdk5 and P2X2R in mouse trigeminal ganglia. Finally, endogenous P2X2aR-mediated currents in PC12 cells and P2X2/3R mediated increases of intracellular Ca 2+ in trigeminal neurons were Cdk5 dependent, since inhibition with roscovitine accelerated the desensitization kinetics of these responses. These results indicate that the P2X2aR is a novel target for Cdk5-mediated phosphorylation, which might play important physiological roles including pain signaling. Abstract : P2X2aR is a novel target for Cdk5-mediated phosphorylation, which might play an important role during pain signaling.